P113. Learning volitional control of functional connectivity: Effects on behaviour. Issue 8 (August 2015) - Kajal, D. Singh; Mellinger, J.; Ruiz, S.; Sacchet, M.; Fetz, E.; Birbaumer, N.; Sitaram, R.; Braun, C.
<x xml:space="preserve">Abstract</x> Cerebral information processing involves the activation of brain regions and the exchange of information between them. As metric for intra-cortical communication, coherence, a frequency specific measure quantifying the correlation of the amplitudes across trials of two phase-locked signals, has been suggested. A value of 0 indicates that both signals are unrelated, a value of 1 that both signals are fully synchronized. It is evidenced by the plethora of findings that the functional connectivity between brain regions is modulated by brain states, mental processing and the planning and execution of actions. Thus, it might be hypothesized that volitionally modulating the functional connectivity between two interacting brain regions should have an impact either on behavior or cognition. The purpose of the study was to test whether subjects can learn to volitionally modulate brain functional connectivity between left and right motor cortices employing a neurofeedback training and whether the neurofeedback training induces specific effects on motor function. Thirty right-handed subjects participated in the study. The subject group was partitioned into two sub-groups, namely contingent feedback group and sham feedback group, consisting of fifteen subjects. During the neurofeedback training the magnetic brain activity originating from left and right primary motor cortices was recorded using magnetoencephalography (MEG) and a feedback signal representing the coherence between the primary motor cortices of both hemispheres was presented to the subjects on a screen. Subjects receiving contingent feedback were trained to increase coherence while the discriminative stimulus SD+ was presented and to decrease coherence while the SD− was presented. A pretest and posttest examination served to examine whether acquired control on functional connectivity evidences any behavioral effects. During pre- and posttest subjects had to perform a complex bimanual finger tapping task while the discriminative stimulus either for up- or down-training was presented. Our findings suggest that it is possible to modulate the functional connectivity between the primary motor cortices of both hemispheres and that changes in functional connectivity do have a strong behavioral impact. Modulating the functional connectivity between brain regions can be used to study the functional role of cortico-cortical connections and will offer therapeutic interventions in brain diseases originating from impaired intra-cortical connections.